A new class of biologic agents facing the therapeutic paradigm in psoriasis: anti-IL-23 agents. (1st February 2018) - Tonini, Annalisa; Gualtieri, Bruno; Panduri, Salvatore; Romanelli, Marco; Chiricozzi, Andrea
ABSTRACT: Introduction : Psoriasis is a chronic inflammatory skin disease whose pathogenesis is driven by multiple cytokine-mediated pathways. In this immunologic setting, the centrality of the IL-23/IL-17 axis and its therapeutic relevance has emerged. Areas covered : This review is aimed at collecting preliminary data on IL23p19 blockers developed for the treatment of plaque psoriasis. Three agents, guselkumab, risankizumab, and tildrakizumab, are currently being tested in phase III trials, while LY2525623 is currently being tested in phase II trials. Treatment with these agents resulted in a marked improvement in disease severity, confirming the pathogenic relevance of IL-23 in psoriasis. Expert opinion : Selective neutralization of IL-23 is an advantageous strategy for treating psoriasis. Preliminary data from phase II and III trials have shown the capability of this therapeutic class in inducing complete clearance or almost complete clearance in many patients: the highest PASI 90 rates were achieved by guselkumab, tildrakizumab, and risankizumab in 73.3%, 74% and 77% of cases, respectively. Moreover, the highest PASI 100 rates were achieved in 33%, 14%, and 48% of patients treated with guselkumab, tildrakizumab, and risankizumab, respectively. Further studies are needed to confirm this remarkable efficacy over long-term treatment periods.